2019
DOI: 10.1016/j.celrep.2019.04.066
|View full text |Cite
|
Sign up to set email alerts
|

Obesity-Associated Hypermetabolism and Accelerated Senescence of Bone Marrow Stromal Stem Cells Suggest a Potential Mechanism for Bone Fragility

Abstract: Highlights d Obesity accelerates differentiation potential of bone marrow stromal stem cells (BM-MSCs) d Obesity shifts molecular phenotype of BM-MSCs toward committed adipocytic progenitors d Obesity increases insulin signaling in BM-MSCs in contrast to adipose tissue-derived MSCs d IR+ and LEPR+ cells in obese BM-MSCs are associated with accelerated senescence

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
100
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(108 citation statements)
references
References 80 publications
7
100
1
Order By: Relevance
“…The authors clearly show that the local signaling of leptin in bone marrow stromal precursors, during obesity, is essential for the adipocyte commitment and differentiation (19). In another work, Tencerova et al (50) showed that LepR-positive BM-MSCs of obese individuals are more likely to differentiate into adipocytes, and that the silencing of LepR in BM-MSCs from obese individuals favored osteogenesis and reduced adipogenesis, with decreased expression of several adipogenesis-associated genes, alongside the impairment of the staining for lipid droplets (50). These results indicate that leptin's local effect may contribute in vivo to adipogenesis.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The authors clearly show that the local signaling of leptin in bone marrow stromal precursors, during obesity, is essential for the adipocyte commitment and differentiation (19). In another work, Tencerova et al (50) showed that LepR-positive BM-MSCs of obese individuals are more likely to differentiate into adipocytes, and that the silencing of LepR in BM-MSCs from obese individuals favored osteogenesis and reduced adipogenesis, with decreased expression of several adipogenesis-associated genes, alongside the impairment of the staining for lipid droplets (50). These results indicate that leptin's local effect may contribute in vivo to adipogenesis.…”
Section: Discussionmentioning
confidence: 93%
“…As stated above, the timing of leptin's treatment is of paramount importance for the outcomes observed in differentiated cells, with an early treatment of precursor cells leading to a proadipogenic leptin signaling. Sustaining this hypothesis, the specific knockout of LepR in already mature adipocytes did not have important effects on adipogenesis (49), while the specific knockout or knockdown of LepR in precursor cells impaired their ability to commit to the adipocyte fate (19,50). Yue et al (19) showed that the specific deletion of the leptin receptor LepR gene in the bone marrow-derived mesenchymal stromal cells (BM-MSCs) favored osteogenesis at the expense of adipogenesis within the bone marrow (19).…”
Section: Discussionmentioning
confidence: 99%
“…Our findings also have implications for BMAT lipid metabolism. Adipocyte-specific ablation of Insr in mice decreases BMAd size 4 , suggesting a role for insulin in BMAd lipogenesis; however, it is unclear if this is through de novo lipogenesis from glucose, via insulin regulating uptake and esterification of fatty acids, or through stimulation by insulin of BMSC adipogenesis 38 . We show that BMAT is capable of insulin-stimulated Akt S473 phosphorylation, a modification implicated in lipogenesis downstream of mTORC2 activation 39 ; however, it is unclear how this might stimulate lipogenesis in the absence of Akt T308 phosphorylation.…”
Section: Discussionmentioning
confidence: 99%
“…33 Another recent study found that, in human bone marrow stromal cells, greater ROS concentrations in obesity enhanced insulin signalling by increasing the abundance of insulin and leptin receptors. 34 The subsequent increase in oxidative phosphorylation of glucose lead to a redox imbalance with ensuing stem cell exhaustion and accelerated bone marrow micro-environment senescence conducive to bone fragility, which is commonly observed in the aged population. Furthermore, excessive ROS in obesity promotes changes in human adipose tissue that are characteristic of ageing.…”
Section: Obesity Induces a Redox Imbalance Similar To Ageingmentioning
confidence: 99%